Virtual contact improves intergroup relations between non-Muslim American and Muslim students from the Middle East, North Africa and Southeast Asia in a field quasi-experiment - Shira Hebel-Sela; Boaz Hameiri; Linda R. Tropp; Samantha L. Moore-Berg; Rebecca Saxe; Eran Halperin; Emile Bruneau (Communications Psychology)
Abstract Given the current polarized climate in many parts of the world, finding effective interventions to address psychological factors that drive conflict is critical. Direct, face-to-face contact has the demonstrated potential to stem the tide of intergroup antipathy. However, modern socio-political conflicts often span great physical distances, making direct contact difficult, costly and rare. Programs for “virtual contact” have emerged in recent years, combining text-based computer-mediated communication with live video to extend intergroup contact’s benefits to broader audiences. While compelling, studies of such programs are typically conducted in laboratory settings, focusing only on change in outgroup attitudes. The current research tests how a semester-long virtual contact intervention that brings together non-Muslim US American students and Muslim students from the Middle East, North Africa and Southeast Asia shapes varied intergroup processes, across two large-scale field quasi-experiments (combined N = 2886). Compared to before the intervention and a control group, participants who engaged in virtual contact showed greater self-outgroup overlap, improved outgroup attitudes, and less outgroup dehumanization and meta-dehumanization. This research provides evidence that virtual contact can be an effective tool for promoting better intergroup relations.